Pengaruh Current Ratio, Debt To Asset Ratio, Return On Assets, Dan Net Profit Margin Terhadap Pertumbuhan Laba (Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2024) - Aini Nur Izzati; Ferry Kosadi (IKRAITH-EKONOMIKA, 2025)
This study examines the impact of Current Ratio (CR), Debt to Asset Ratio (DAR), Return on Assets (ROA), and Net Profit Margin (NPM) on profit growth among transportation companies listed on the Indonesia Stock Exchange (BEI) from 2017-2024, employing multiple linear regression analysis via SPSS with secondary data from annual financial reports. A quantitative approach with descriptive and verificative characteristics was utilized. Findings reveal that partially, CR and DAR exhibit significant negative effects, NPM shows a significant positive effect, while ROA demonstrates no significant impact on profit growth. Simultaneously, all four ratios significantly influence profit growth, with an Adjusted R² of 94.7%, indicating that financial ratios explain most variations, and the remainder stems from external factors.